Análise e superação de algumas dificuldades na calibração automática do modelo SMAP-II - versão suavizada - Thomaz, Fernanda Rocha (1992)
The rainfall-runoff models are used to simulate the physical processes which occur in a basin during the land phase of the hydrological cycle. To represent and link the physical processes, mathematical functions are used in which formulation there are parameters estimated by manual or automatic calibration. The calibration is one of the most difficult and arduous phases in the simulation process. This work analyses the difficulties encountered in the automatic calibration of the SMAP-II model, smoothing version. A possible interdependence between the parameters of the channel phase and the runnoff recession coefficient is investigated from analysis of the response surface, the sensivity ratio calculation and also the channel phase equations development. ln order to overcome the difficulties two strategies are presented: The first one is related to the choice of the parameters initial values and the second consists in the channel phase reformulation. Finally, the results of a parameter sensivity study belonging to the method of Hyperbolic Penalty are presented. This method is responsible for the parameters maintainance in the feasible region.